Video Transects Reveal That Tidal Sand Waves Affect the Spatial Distribution of Benthic Organisms and Sand Ripples. Issue 21 (8th November 2018) - Damveld, J. H.; van der Reijden, K. J.; Cheng, C.; Koop, L.; Haaksma, L. R.; Walsh, C. A. J.; Soetaert, K.; Borsje, B. W.; Govers, L. L.; Roos, P. C.; Olff, H.; Hulscher, S. J. M. H.
Abstract: The sandy seabed of shallow coastal shelf seas displays morphological patterns of various dimensions. The seabed also harbors a rich ecosystem. Increasing pressure from human‐induced disturbances necessitates further study on drivers of benthic community distributions over morphological patterns. Moreover, a greater understanding of the sand ripple distribution over tidal sand waves may improve morphological model predictions. Here we analyzed the biotic abundance and ripple morphology in sand wave troughs and crests using video transects. We found that both the epibenthos and endobenthos are significantly more abundant in sand wave troughs, where ripples are less abundant and more irregularly shaped. Finally, we show that camera systems are relatively quick and effective tools to study biotic spatial patterns in relation to seabed morphology. Plain Language Summary: Coastal seabeds are important areas for human activities and constructions and are also inhabited by many organisms, collectively referred to as benthos. The interaction of tides, wind, sand and biology leads to the growth of large, rhythmic seabed patterns. They can grow up to several meters high, hundreds of meters long, and shift a few meters per year. Computer models can predict this behavior, but they lack understanding of biological processes and variations in sand ripple patterns. To increase the understanding of these effects, we present findings from two video transects, for which we lowered a video camera to the seabed and recorded both organisms and sand ripples for 200 m. We show that, relative to crests, troughs have more benthic organisms, and sand ripples are often absent or less regularly shaped. Finally, we show that a camera is a quick and effective tool to study benthic spatial patterns. Key Points: Video transects over tidal sand waves yielded detailed spatial information of both benthic organisms and small‐scale seabed morphology Both epibenthos and endobenthos are more abundant in sand wave troughs compared to the crests Sand ripples are less abundant and more often irregularly shaped in the troughs, suggesting variations in seabed roughness over sand waves